Tata Cara Penyajian Tari Persembahan Bungo Dalam Acara Penyambutan Tamu Di Kabupaten Bungo Provinsi Jambi - Lidya Indrawati; Indrayuda Indrayuda (SENDRATASIK UNP, 2020)
This study aims to reveal the procedures for presenting Persembahan Bungo dance in a guest welcoming event in Bungo Regency, Jambi Province. This is a qualitative research resulting descriptive analysis data. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing instruments and cameras. The data used were primary and secondary data. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted bycollecting the data, reducing the data, presenting the data, and making conclusion. The results show that Persembahan Bungo dance has parts and sequences in each presentation. They are preparation before performing, initial stage, during the performance, and the end of the performance.Persembahan Bungo dance has 9 movements: Sembah Penghormatan, gerak selamat datang, sembah paduko, lenggang, putri malu, berinai, limbai, zapin bungo, and mambuko pagar ayu. The rules for performing Persembahan Bungo dance are compiled by custom or according to the customary rules in Bungo Regency, are in accordance with the motto of Bungo Regency, and pay attention to the values in a reception. For example, in the rule of washing betel, the betel must be washed first by the queen. This symbolizes cleanliness, purity, and respect for the welcomed guests by people of Bungo regency.